The Impact of Effective Leadership on Student Achievement - ALOMAR, NISRIN (2025)
Effective leadership is one of the most crucial aspects of ensuring successful student achievement. This is applicable especially in schools that are underperforming and facing true challenges, such as lack of resources, low teacher morale, and high teacher turnover rates. This research study enlightens the impact of different leadership styles, such as transformational leadership, distributed leadership and instructional leadership, on student accomplishments. A mixed-method research model was used to collect qualitative data from 7 school leaders through interviews and quantitative data from 25 participants through surveys . The collected data assisted in examining the leadership efficiency of school leaders in term of influencing student learning outcomes. The research underlined that resource allocation, teacher motivation, professional development, and strategic vision are some key determinants of student performance. According to obtained findings, transformational leadership has been identified as having the ability to steer innovative teaching strategies, engagement and collaboration. However, in spite of having certain benefits, school leaders experience different challenges like restricted financial support, maintaining teacher motivation and policy-related restrictions. The research recommended that involving teachers in decision-making process, conducting leadership development workshops, and well-directed coaching sessions to overcome the identified barriers. This aims to ensure optimal leadership efficiency while working with underperforming schools to enhance students’ learning outcomes.